The quilt - Paulsen, Gary. (New York : Wendy Lamb Books, 2005)
During World War II, while his father is in Europe fighting and his mother is working in Chicago, a five-year-old boy goes to live with his grandmother in a rural Norwegian American community in Minnesota. Based on events from the author's life.
"A companion to Alida's song" --Cover.
G9
Keywords: Grandmothers -- Fiction; Norwegian Americans -- Fiction; World War, 1939-1945 -- United States -- Fiction; Childbirth -- Fiction